The SDGs and the migrant civil society. The fit of immigrant assocations in the policies of cooperation for development in Spain - Lacomba, Joan; Royo, Isabel (Iberoamerican Journal of Development Studies, 2020)
Spanish cooperation introduced in the recent past new policies linking migration and development under the name of «co-development». One of the novel elements of co-development was the promotion of the role of immigrants as agents of development, as well as the strengthening of relations between NGODs and immigrant associations, constituted the latter in a new actor of Spanish civil society. The objective of this article is to make a balance of the results of this policy —particularly in the autonomous sphere—, showing how, despite the broad expectation that it generated in terms of a novel structure of political opportunity, the co-development would have had some rather limited results. For this, we rely on the evidence of two research projects at national level, and the analysis of the plans and calls of the Spanish autonomous communities in development cooperation.